Beneficial Effects of Macroporous Resin Extract of Dendrobium candidum Leaves in Rats with Hyperuricemia Induced by a High-Purine Diet. (3rd February 2020) - Lou, Xiao-Jing; Wang, Yu-Zhi; Lei, Shan-Shan; He, Xinglishang; Lu, Ting-Ting; Zhan, Liang-Hui; Chen, Xue; Chen, Ye-Hui; Li, Bo; Zheng, Xiang; Lv, Gui-Yuan; Chen, Su-Hong
Abstract : Objectives . The incidence of hyperuricemia (HUA) is increasing year by year, and there are no ideal drugs for the treatment; the existing ones can cause serious liver and kidney damage. We have confirmed that the water extract of Dendrobium candidum leaves could reduce the level of uric acid in rats, but the active ingredients remain unknown, and the mechanism is not well understood. This research investigated the therapeutic effect of the macroporous resin extract of the Dendrobium candidum leaf (DLE) on hyperuricemia. In this study, hyperuricemia was induced in rats by a 5-week high-purine diet. After that, DLE was administered continuously for 9 weeks. The result showed that biochemical parameters of liver and kidney function, especially serum uric acid (UA) levels, were significantly improved with DLE, which may relate to the reduction of xanthine oxidase (XOD) and adenosine deaminase (ADA) in the liver. Moreover, DLE could significantly prevent kidney and liver from damage, and intestinal injury and reduce inflammation in hyperuricemic rats by inhibiting the expression of both NF- κ B and TLR4 proteins. These results showed that the macroporous resin extract of the Dendrobium candidum leaves may be effective for the treatment of hyperuricemia in rats by inhibiting uric acid production and decreasing inflammation.